Column Flotation of Coals and Minerals with Oscillatory Air Supply (International Mineral Processing Congress, 2018)
"This research aims at improving the beneficiation of coals and minerals in fine and ultrafine size fractions. A widely used method for upgrading fine and ultrafine particles is froth flotation, which is generally classified into mechanical flotation and column flotation. The present work is focussed on column flotation. A flotation column equipped with a conventional bubble diffuser/sparger was used with oscillatory air supply generated using a fast-switching solenoid valve. The flotation tests were carried out for coal particles and mineral particles, respectively, and a comparison in flotation performance was made between oscillatory air supply and steady air supply. It was found that use of oscillatory air supply with a proper valve switching frequency and on/off time ratio to replace steady air supply could lead to increased recovery of coals or minerals by more than 14 percentage points and substantial reagent cost savings. The improved flotation performance was attributed to enhanced gas dispersion and flow conditions. This research offers a simple new approach to improving the beneficiation of fine coals and minerals with using flotation columns.INTRODUCTIONFroth flotation has been widely used for the separation and concentration of fine coals and minerals by exploiting the difference in their affinity to air bubbles in aqueous medium. Froth flotation is an effective method for beneficiation of coal and mineral particles in a certain size range. It remains difficult to upgrade ultrafine mineral particles. One of the reasons for the ineffective flotation of fine particles is the low probability of bubble-particle collision in the collection zone (i.e., the pulp zone). According to Reay and Ratcliff (1973) and Yoon and Luttrell (1989), the probability of collision is significantly affected by bubble size and particle size, and the collection zone recovery can be increased by decreasing the bubble size."